2003
DOI: 10.1046/j.0001-690x.2003.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled randomized treatment study: the effects of a cognitive remediation program on adolescents with early onset psychosis

Abstract: Based on these results we cannot conclude that the addition of this cognitive remediation program, yields better results than psychoeducation alone. However, within-group analyses indicate that on specific cognitive functions, as well as on some functioning outcome measures, the remediation program may have a positive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 18 publications
2
76
0
2
Order By: Relevance
“…Alternatively, it may be that some, but not all, of the cognitive functions measured by our assessment battery are amenable to the intervention taken here. Overall, however, our findings are in line with earlier reports that show that targeted, repeated interventions can partially remediate altered function in psychiatric illness, most prominently schizophrenia (Bell et al 2001(Bell et al , 2003Fiszdon et al 2004 ; but see van der Gaag et al 2002 ;Ueland & Rund, 2004 for exceptions), and extend these finding to MDD. Moreover, these performance gains occurred as the result of an easily administered, computerized intervention (Bracy, 1994) that minimizes the output of resources and is relatively inexpensive to acquire and to administer.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, it may be that some, but not all, of the cognitive functions measured by our assessment battery are amenable to the intervention taken here. Overall, however, our findings are in line with earlier reports that show that targeted, repeated interventions can partially remediate altered function in psychiatric illness, most prominently schizophrenia (Bell et al 2001(Bell et al , 2003Fiszdon et al 2004 ; but see van der Gaag et al 2002 ;Ueland & Rund, 2004 for exceptions), and extend these finding to MDD. Moreover, these performance gains occurred as the result of an easily administered, computerized intervention (Bracy, 1994) that minimizes the output of resources and is relatively inexpensive to acquire and to administer.…”
Section: Discussionsupporting
confidence: 92%
“…A recent review of eight published manuscripts concluded that preliminary results are positive, but more empirical research is needed to confirm the efficacy of cognitive remediation (Barlati et al, 2012). For example, one study of cognitive remediation in adolescents with early onset psychosis initially found no superior effect of cognitive remediation compared to psychoeducation, but at one year follow-up there appeared to be an effect on early visual information processing (Ueland and Rund, 2004;Ueland and Rund, 2005). Other studies have found positive effects of cognitive remediation for early course schizophrenia on global cognition (Eack et al, 2009;Fisher et al, 2015), learning (Fisher et al, 2015), executive functioning (Wykes et al, 2007;Fisher et al, 2015), social cognition (Eack et al, 2009), psychiatric symptoms (Eack et al, 2009), and social adjustment (Eack et al, 2009(Eack et al, , 2010b.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, only 11 studies evaluated functional outcomes (16,19,20,22,24,25,27,29,(42)(43)(44), and this was the first meta-analysis to quantitatively demonstrate that cognitive remediation improved psychosocial functioning. Furthermore, the impact of cognitive remediation on functioning was moderated by several factors, including the provision of adjunctive psychiatric rehabilitation, cognitive training method, and patient age, suggesting potentially important factors for improving the impact of treatment programs.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Despite the number of controlled studies of cognitive remediation, only six studies (16,19,21,(28)(29)(30) examined whether improvements in cognitive functioning were maintained at a posttreatment follow-up, precluding the exploration of moderators of treatment effects. The relative lack of data addressing this question may be important because different program, patient, or setting factors could influence the long-term maintenance of cognitive effects compared to short-term effects.Similarly, only 11 studies evaluated functional outcomes (16,19,20,22,24,25,27,29,(42)(43)(44), and this was the first meta-analysis to quantitatively demonstrate that cognitive remediation improved psychosocial functioning. Furthermore, the impact of cognitive remediation on functioning was moderated by several factors, including the provision of adjunctive psychiatric rehabilitation, cognitive training method, and patient age, suggesting potentially important factors for improving the impact of treatment programs.…”
mentioning
confidence: 99%